Corporate engagement in mitigating plastic pollution: examining voluntary initiatives and EU regulations - Bokor, Barbara (Frontiers in Sustainability, 2024)
Plas c pollu on has emerged as a cri cal global environmental challenge, with far-reaching ecological, economic, and social implica ons. This ar cle addresses the fragmented nature of the current literature on plas c pollu on regula ons and their impact on the corporate sector and aims to bridge this gap by providing a comprehensive analysis of the current EU regulatory framework and corporate voluntary self-regulatory ini a ves relevant to plas c pollu on. Examining voluntary ini a vesincluding corporate social responsibility (CSR) programs and the emerging concept of plas c creditsin terms of their poten al to tackle plas c pollu on and promote environmental sustainability, the ar cle presents novel insights on how different regulatory mechanisms and voluntary self-regulatory ini a ves engage the corporate sector in mi ga ng plas c pollu on. While highligh ng the importance of collabora ve efforts between regulatory bodies and businesses, the study cri cally evaluates the challenges and limita ons of current approaches. It addresses concerns about the efficacy and transparency of CSR ini a ves, with par cular a en on to the issue of greenwashing and its poten al legal implica ons. By synthesizing diverse sources, this ar cle emphasizes the need to combine stringent regulatory frameworks with responsible business prac ces to engage the corporate sector in preven ng and mi ga ng plas c pollu on, specifically within the context of the European Union's pioneering environmental policy. Ul mately, the study suggests that the most effec ve long-term solu on lies in reducing plas c produc on altogether while acknowledging the role of transi onal measures in the interim.